Lessons Learned From Beta-Testing a Facebook Group Prototype to Promote Treatment Use in the "Connecting Alaska Native People to Quit Smoking" (CAN Quit) Study - Pamela S Sinicrope; Colleen D Young; Ken Resnicow; Zoe T Merritt; Clara R McConnell; Christine A Hughes; Kathryn R Koller; Martha J Bock; Paul A Decker; Christie A Flanagan; Crystal D Meade; Timothy K Thomas; et al. (JMIR Publications, 2022)
Social media provides an effective tool to reach, engage, and connect smokers in cessation efforts. Our team developed a Facebook group, CAN Quit (Connecting Alaska Native People to Quit smoking), to promote use of evidence-based smoking cessation resources for Alaska Native people living in Alaska, which are underused despite their effectiveness. Often separated by geography and climate, Alaska Native people prefer group-based approaches for tobacco cessation that support their culture and values. Such preferences make Alaska Native people candidates for social media-based interventions that promote connection. This viewpoint discusses the steps involved and lessons learned in building and beta-testing our Facebook group prototype, which will then be evaluated in a pilot randomized controlled trial. We describe the process of training moderators to facilitate group engagement and foster community, and we describe how we developed and tested our intervention prototype and Facebook group. All parts of the prototype were designed to facilitate use of evidence-based cessation treatments. We include recommendations for best practices with the hope that lessons learned from the CAN Quit prototype could provide a model for others to create similar platforms that benefit Alaska Native and American Indian people in the context of smoking cessation.